THE PROCESS OF ONLINE LEARNING IN READING AT THE EIGHTH-GRADE OF SMP N 18 SURAKARTA - Ria Santika (English Education Department Slamet Riyadi University Surakarta, 2020)
This research was concerned on the process of online learning especially in reading at the eighth-grade of SMP N 18 Surakarta . This study used descriptive qualitative to describe the process of online learning in reading at the eighth grade of SMP N 18 Surakarta. In this research the researcher was used questionnaire and interview to collected the data. In analyzed the data, the researcher used data reduction, data display, and data verification. From the students questionnaire, students interview and teacher interview, the researcher was found that the teacher used the grammar-translation method to teach reading in online learning. The media used by the teacher to teach reading in online learning is Visual-Media. The difficulties faced by the students are the students not understanding the questions given by the teacher, there are some students who don’t have smartphone and internet quotas, there are some students who are lazy to do their assignment. The problems faced by the teacher is the teacher can not monitor their students directly. The strategy used by the teacher to teach reading in online learning is Independent Study. Keyword: Qualitative Research, Descriptive Study, Online Learning, Reading.